2007
DOI: 10.1002/bip.20818
|View full text |Cite
|
Sign up to set email alerts
|

Astressin‐amide and astressin‐acid are structurally different in dimethylsulfoxide

Abstract: The C-terminally amidated CRF antagonist astressin binds to CRF-R1 or CRF-R2 receptors with low nanomolar affinity while the corresponding astressin-acid has >100 times less affinity. To understand the role of the amide group in binding, the conformations of astressin-amide and astressin-acid were studied in DMSO using NMR techniques. The 3D NMR structures show that the backbones of both analogs prefer an alpha-helical conformation, with a small kink around Gln(26). However, astressin-amide has a well-defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…3). The positioning of this kink is similar to the kinks observed for CRF family ligands in the solvent DMSO (48) but is absent in all the other ligands of family B1 when they are bound to their respective ECD1s in the crystal structures. Although the role of this kink may be understood only in the context of the full-length receptor, it enlarges the conformational space of the N-terminal peptide segment, which is possibly important for receptor-specific signaling (Fig.…”
Section: Three-dimensional Structure Of the Ecd1-crf-r1supporting
confidence: 63%
See 1 more Smart Citation
“…3). The positioning of this kink is similar to the kinks observed for CRF family ligands in the solvent DMSO (48) but is absent in all the other ligands of family B1 when they are bound to their respective ECD1s in the crystal structures. Although the role of this kink may be understood only in the context of the full-length receptor, it enlarges the conformational space of the N-terminal peptide segment, which is possibly important for receptor-specific signaling (Fig.…”
Section: Three-dimensional Structure Of the Ecd1-crf-r1supporting
confidence: 63%
“…5). These hydrogen bonds explain the necessity of C-terminal amidation for high affinity recognition of CRF ligands (48,51 …”
Section: Three-dimensional Structure Of the Ecd1-crf-r1mentioning
confidence: 97%
“…Here we confirm the role of Arg 23 and Glu 25 in the interaction between r/hCRF and CRF-BP, as alanine substitution of these peptide residues results in a loss of affinity of 7-and 80-fold, respectively. A closer inspection of the core residues of CRF in their ␣-helical conformation reveals that Glu 25 and Arg 23 are the only polar residues amid an otherwise hydrophobic face of the ␣-helical CRF peptide (37,38). The amino acid side chains of Arg 23 and Glu 25 occupy the same face of the CRF peptide but point in opposite directions (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It took several additional trials before we identified the cyclo (Glu i -Lys i+3 ), and not (Lys i -Glu i+3 ), as the best ring size and composition (Gulyas et al, 1995; Miranda et al, 1994) for side chain stabilization, at a time when published work used mostly cyclo(Xaa i -Xbb i+4 ) scaffolds (Grace et al, 2007a). The discovery of astressin with increased in vitro potency (32.5 times that of DPhe 12 CRF or DPhe 12 C α MeLeu 37 , RAP assay (Table 2) and binding affinity to both CRFR 1 and CRFR 2 over that of [DPhe 12 ,Nle 21,38 ]-r/h CRF (12–41) and [DPhe 12 ,Nle 21,38 ,C α MeLeu 37 ]-r/h CRF (12–41) (Table 2), resulted from constraining the structure of [DPhe 12 ,Nle 21,38 ]-r/h CRF (12–41) further through the introduction of a lactam bridge (see Table 1 and below).…”
Section: Crfmentioning
confidence: 99%
“…Predictive methods, physicochemical measurements, and structure-activity relationship studies have suggested that CRF, its family members, and competitive antagonists such as astressin {cyclo(30–33)-[DPhe 12 ,Nle 21 ,Glu 30 ,Lys 33 ,Nle 38 ]hCRF (12–41) }, assume an α- helical conformation when interacting with their receptors (Grace et al, 2010; Grace et al, 2007b; Koerber et al, 1998). As indicated earlier, we had shown that α-helical CRF (9–41) and sauvagine exhibited some selectivity for CRF receptors other than that responsible for ACTH secretion, and later for CRF 2 binding (Perrin et al, 1999).…”
Section: Crfmentioning
confidence: 99%